Arts Entrepreneurship Creating a New Venture in the Arts. - Andrews, Richard S. (Independence : Routledge, 2019)
Arts Entrepreneurship: Creating a New Venture in the Arts provides the essential tools, techniques, and concepts needed to invent, launch, and sustain a business in the creative sector. Building on the reader's artistic talents and interests, the book provides a practical, action-oriented introduction to the business of art, focusing on product design, organizational planning and assessment, customer identification and marketing, fundraising, legal issues, money management, cultural policy, and career development. It also offers examples, exercises, and references that guide entrepreneurs through the key stages of concept creation, business development, and growth. Special attention is paid to topics such as cultural ventures seeking social impact, the emergence of creative placemaking, the opportunities afforded by novel corporate forms, and the role of contemporary technologies in marketing, fundraising, and operations. A hands-on guide to entrepreneurial success, this book is a valuable resource for students of Arts Entrepreneurship programs, courses, and workshops, as well as for early-stage business founders in the creative sector looking for guidance on how to create and sustain their own successful venture.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: PERFORMING ARTS / Theater / General; BUSINESS & ECONOMICS / Entrepreneurship; Arts -- Management; Arts -- Economic aspects